Stathmin expression alters the antiproliferative effect of eribulin in leiomyosarcoma cells - Mana Azumi; Mikihiro Yoshie; Nami Nakachi; Atsuya Tsuru; Kazuya Kusama; Kazuhiro Tamura (Elsevier, 2022)
Uterine leiomyosarcoma is an aggressive soft tissue tumor. Stathmin, a phosphoprotein that modulates microtubule dynamics, is highly expressed in many malignancies including leiomyosarcoma. The microtubule-depolymerizing agent eribulin has been recently approved for treating malignant soft tissue tumors. Although eribulin inhibits microtubule polymerization, little is known about the relationship between eribulin treatment and stathmin dynamics. In this study, we explored the role of stathmin expression in the action of eribulin in leiomyosarcoma cells. Eribulin induced phosphorylation of stathmin and reduced expression of subunits A and C of protein phosphatase 2A (PP2A) in a leiomyosarcoma cell line. The PP2A activator FTY720 reduced levels of phosphorylated stathmin. Eribulin decreased stathmin protein levels without affecting stathmin mRNA expression. Furthermore, stathmin knockdown attenuated the inhibitory effects of eribulin on cell viability, whereas stathmin overexpression enhanced the anti-proliferative effect of eribulin. Eribulin-resistant leiomyosarcoma cell lines had enhanced expression of the class Ⅰ β-tubulin TUBB1, multi-drug resistance 1 protein MDR1 and breast cancer-resistance protein BCRP, and decreased expression of stathmin. Taken together, these results suggest that stathmin expression modulates the pharmacological efficacy of eribulin in uterine leiomyosarcoma cells.